Hydrating Balm Serum Minyak Cendana (Santalum album L.) dan Minyak Zaitun (Olea europaea) untuk Meningkatkan Kelembapan Kulit - Vica Aspadiah; Astrid Indalifiany; Suryani Suryani; Nur Illiyyin Akib; Rahmat Muliadi; Wa Ode Sitti Aminah Basri (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2026)
Dry skin is associated with barrier dysfunction and decreased hydration of the stratum corneum. Santalum album and Olea europaea contain bioactive compounds that function as emollients and occlusives. A serum balm formulation with a high concentration of active ingredients has the potential to effectively restore skin moisture. This study aimed to determine the optimal composition of a serum balm formula, identify the physical characteristics and stability of the formulation using the cycling test method, and evaluate the moisturizing effectiveness of a serum balm containing sandalwood oil and olive oil. The method involved formulating a serum balm with varying concentrations of sandalwood oil as the active ingredient, followed by evaluation of physical characteristics including organoleptic properties, pH, homogeneity, spreadability, and adhesiveness. Stability testing was conducted using the cycling test method by storing the preparation at 4°C for 24 hours and then transferring it to room temperature (25°C) for another 24 hours. The effectiveness test was performed using an in vitro occlusivity method. The results showed that the serum balm formulations were homogeneously distributed, had a pH of approximately 5, spreadability of 3.2–3.6 cm, and adhesiveness ranging from 9–22 seconds. The physical stability test indicated that the formulations met the required standards, and the moisturizing effectiveness ranged from 30–62%. In conclusion, the most optimal formula was F5 with 10% sandalwood oil, as it demonstrated the highest moisturizing activity at 61.095% before the cycling test and 54.965% after the cycling test, while also fulfilling the required physical characteristics.